A Model of Women's Empowerment through the Salimah Rumah Education Program in Improving the Quality of Prosper Family in Lampung Central District - Sari, Ariyana; Ghazali, Bahri; Makmun, Fariza; Yanti, Fitri (LPPM Universitas Bumigora, 2023)
Islam sees men and women have the same degree that distinguishes only the level of ketaqwaannya only. Women are one of the elements of society that has its role and function. Women as equal partners of men should be able to optimize their strategic role in a development. This study aims to determine (1) the model of women empowerment through Rumah pendidikan Salimah and (2) the impact of empowerment in improving the quality of prosperous families. The technique of data collection is done by interview, observation, and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions. The results showed that the model of women empowerment was carried out through the establishment of “Rumah Pendidikan Salimah” and the impact of empowerment that was carried out was seen from the process that was systematically arranged and had an applicable impact on the people of Central Lampung as evidenced by the maintenance of good relations in the family and the fulfillment of healthy and prosperous family indicators based on BKKBN.